Comparison of electro-thermal performance of advanced cooling techniques for electric vehicle motors. (25th January 2021) - Tikadar, Amitav; Johnston, David; Kumar, Nitish; Joshi, Yogendra; Kumar, Satish
Highlights: Effectiveness of four different cooling technologies have been studied numerically. Direct stator cooling configurations provide poor electro-magnetic performance. Direct winding cooling approach provides best electro-thermal performance. Abstract: Permanent magnet synchronous motors are commonly used in the powertrain of electric vehicles because of their high power and torque densities. Attempts to increase power and torque densities beyond the state-of-the-art often suffer from thermal limitations of the adopted winding-wire insulation class. In this paper, overall effectiveness of four different cooling technologies, namely conventional stator jacket cooling, embedded circular and rectangular cooling channel within stator core, and direct winding heat exchanger have been studied numerically. By realizing temperature dependent magnetic and material properties, winding and core losses, a two-way coupling algorithm has been utilized to study the detailed electro-magnetic and thermal performance of BMW i3 motor with aforementioned cooling techniques. The numerical results illustrate that the direct winding heat exchanger approach provides better electro-thermal performance in comparison to the other cooling techniques analyzed. On the contrary, embedded rectangular and circular channel in stator core adversely affect the electro-magnetic performance and overall efficiency of the motor, despite their superior thermal performance compared to the jacket cooling.